2022
DOI: 10.1101/2022.08.16.504073
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SWIP mediates retromer-independent membrane recruitment of the WASH complex

Abstract: The pentameric WASH complex facilitates endosomal protein sorting by activating Arp2/3, which in turn leads to the formation of F-actin patches specifically on the endosomal surface. It is generally accepted that WASH complex attaches to the endosomal membrane via the interaction of its subunit FAM21 with the retromer subunit VPS35. However, we observe the WASH complex and F-actin present on endosomes even in the absence of VPS35. We show that the WASH complex binds to the endosomal surface in both a retromer-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…It is likely our data can be reconciled through the complex multivalent nature of FAM21 association with Retromer, such that although the VPS35 interaction with FAM21 reduces WASH interaction significantly (Figure 2G and 2H), and is required for a proportion of WASH recruitment to endosomal retrieval domains, the other minor sites in VPS29 retain an ability to engage FAM21 and may compensate for its loss. Further, FAM21 can interact with SNX27 and other endosomal proteins such as the Commander complex (25,49), and the population of WASH associated with endosomes in the asbence of Retromer as seen here (Figure 6A) and in other studies (50) provide an added level of potential compensation.…”
Section: Vps35 Sites 1 and 2 Enhance Wash Endosomal Recruitment But A...supporting
confidence: 65%
See 3 more Smart Citations
“…It is likely our data can be reconciled through the complex multivalent nature of FAM21 association with Retromer, such that although the VPS35 interaction with FAM21 reduces WASH interaction significantly (Figure 2G and 2H), and is required for a proportion of WASH recruitment to endosomal retrieval domains, the other minor sites in VPS29 retain an ability to engage FAM21 and may compensate for its loss. Further, FAM21 can interact with SNX27 and other endosomal proteins such as the Commander complex (25,49), and the population of WASH associated with endosomes in the asbence of Retromer as seen here (Figure 6A) and in other studies (50) provide an added level of potential compensation.…”
Section: Vps35 Sites 1 and 2 Enhance Wash Endosomal Recruitment But A...supporting
confidence: 65%
“…These studies also identified the 21 LFa repeats in the FAM21 tail and their importance for Retromer association (Jia et al, 2012). The C-terminal tail of FAM21 is sufficient for endosomal localisation (Harbour et al, 2012), and Retromer is important for endosomal recruitment of WASH (Harbour et al, 2010;Helfer et al, 2013;Jia et al, 2012;McGough et al, 2014b;Zavodszky et al, 2014), although WASH can also be recruited through Retromer-independent mechanisms via FAM21 and WASHC4/SWIP subunits respectively (Dostál et al, 2022). WASH depletion was also reported to result in exaggerated endosome-derived tubules (Derivery et al, 2009;Gomez & Billadeau, 2009;Ryder et al, 2013), although this is not universally observed (Buckley et al, 2016;Lee et al, 2016;McGough et al, 2014a;Miller et al, 2018).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations